IMPLEMENTASI KEBIJAKAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA LOWIAN KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - Supit, Johnetha Lafani; Nangoi, Grace B.; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The Indonesian Nation is part of the world community that has to participate in realizing a good government to support in the competition in the current era of globalization. Ministerial Regulation No. 113 of 2014 on the management of village finances. As referred to in Article 5 of the Minister of Home Affairs Number 113 of 2014 on preparing and implementing polices on the management of the Village Revenue and Expenditure Budget. Budget revenue and village spending is one of the things that must be considered to realize good governance in the village. The purpose of this study is to find out whether the implementation of revenue and expenditure budget policies runs well in accordance with Ministerial Regulation number 113 of 2014, and any constraints faced in implementing the policy of the village income and expenditure budget. The method used is qualitative descriptive method that is analyzing how the implementation of Village Revenue and Expenditure budget policy from planning to accountability. The result of the research show that the implementation of Village Revenue and Expenditure Budget policy in Lowian Village is good enough and has been in accordance with Ministerial Regulation No. 113 Year 2014 on the management of village finances but the problem is on the external side where the trees are located next to the road and plots of land owned by citizens, as well as village officials who still do not really understand the technical reporting making. Keywords: Policy Implementation, Accountability, Village Revenue and Expenditure Budget